2013
DOI: 10.1080/00220388.2013.841887
|View full text |Cite
|
Sign up to set email alerts
|

How Access to Irrigation Influences Poverty and Livelihoods: A Case Study from Sri Lanka

Abstract: This study combines a livelihoods approach with a regression approach to quantify the effectiveness of irrigation infrastructure investment on improving people's livelihood strategies. Using a unique dataset based on households in southern Sri Lanka, and a natural experimental setting, we estimate from a two stage income regression model to show that irrigation access has a positive effect on income through livelihood choices. We also show through qualitative approaches that factors not linked to irrigation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In terms of poverty reduction for an average household, access to large-scale irrigation reduces poverty by 12 percentage points. Sellamuttu et al (2014) present observational evidence that surface irrigation reduces both chronic and transient poverty, which likely reflects the aforementioned impacts on both the mean level and variability of agricultural production.…”
Section: Downstream Impacts On Povertymentioning
confidence: 69%
“…In terms of poverty reduction for an average household, access to large-scale irrigation reduces poverty by 12 percentage points. Sellamuttu et al (2014) present observational evidence that surface irrigation reduces both chronic and transient poverty, which likely reflects the aforementioned impacts on both the mean level and variability of agricultural production.…”
Section: Downstream Impacts On Povertymentioning
confidence: 69%
“…Nonetheless, due to Pakistan's arid and semi-arid climatic conditions, about 90% of the area in Pakistan is irrigated through canal irrigation which is approximately 56,073 kilometers and supplemented through groundwater (Iqbal, 2015). A recent study in Sri Lanka has shown that irrigation water access has a positive effect on income through livelihood choices (Senaratna Sellamuttu et al, 2014). Similarly, in a study, Ahmad (1993) found that improved water-management practices contribute to the increase in net return at the farm household level.…”
Section: Introductionmentioning
confidence: 98%
“…The effective management of farm irrigation system facilities is the ground for enhancing the entire agricultural production capacity and has substantial practical significance for boosting food yield and unravelling hunger and poverty (Ahmed, 2022; Bacha et al, 2011; Postel et al, 2001; Sellamuttu et al, 2014). However, farm irrigation systems are weakly exclusive and competitive within geographical areas or specific management scopes.…”
Section: Introductionmentioning
confidence: 99%